Police-related deaths in the United States - Baker, David (Policing perspectives and challenges in the twenty-first century, 2021)
Cover -- Contents -- Preface -- Acknowledgments -- List of Abbreviations -- Introduction: Who Counts? -- "Comply or Die" -- Suspect Populations -- They Musta Done Somethin' -- Move On, Nothing to See Here -- Blue Codes and Bad Apples -- Walk in My Shoes -- Business as Usual? -- Bibliography -- Index -- About the Author